The regulation of new police authorities in the Police Act - Milidragović Dragan; Milić Nenad (Zbornik Radova Pravnog Fakulteta u Nišu, 2023)
The advent of modern technologies and their implementation into various spheres of human activities, including security, facilitated a faster development of the society, while increasing the risk of human rights violations. In that context, an emerging challenge is how to maximize the use of new technological features while still preserving citizens' rights and freedoms. The application of all measures, actions and tools in police work must be based on the adequate legal framework which clearly regulates the police authorities. Standardizing new police authorities is not an easy task; it requires coordination and finding the right balance between security, law and human rights. This paper addresses the regulation of police authorities in the Police Act of the Republic of Serbia. The authors analyze the operational capabilities of modern technologies and other instruments that may be used in police operations and propose specific normative grounds for their application by defining four new police authorities. The authors point out to the role, significance and use of the proposed new police authorities in future police work, urging that they should be introduced as new legal rules in subsequent amendemnts of the Police Act.